MiR-30a-5p suppresses breast tumor growth and metastasis through inhibition of LDHA-mediated Warburg effect. (1st August 2017) - Li, Ling; Kang, Lei; Zhao, Wei; Feng, Yingying; Liu, Wenpeng; Wang, Tao; Mai, Haixing; Huang, Jun; Chen, Siyu; Liang, Yingchun; Han, Juqiang; Xu, Xiaojie; et al.
Abstract: Lactate dehydrogenase A (LDHA), a key enzyme regulating aerobic glycolysis, is overexpressed in many human cancers, and correlates with poor clinical outcomes. Aerobic glycolysis is a hallmark of cancer, and drugs targeting its regulators, including LDHA, are being developed. However, the mechanisms of LDHA inhibition and the physiological significance of the LDHA inhibitors in cancer cells are unclear. Here, we show that microRNA-30a-5p (miR-30a-5p) suppresses LDHA expression by directly targeting its 3′-UTR. Through inhibition of LDHA, miR-30a-5p dampens glycolysis by decreasing glucose uptake, lactate production, ATP generation, and extracellular acidification rate (ECAR), and increasing oxygen consumption rate (OCR) in breast cancer cells. Importantly, glycolysis regulated by miR-30a-5p is critical for its regulating breast tumor growth and metastasis both in vitro and in vivo. In breast cancer patients, miR-30a-5p expression is negatively correlated with LDHA expression. Moreover, patients who had increased glucose uptake in tumors assessed by PET scans showed decreased miR-30a-5p expression and increased expression of LDHA. Our findings provide clues regarding the role of miR-30a-5p as a tumor suppressor in breast cancer through the inhibition of LDHA. Targeting LDHA through miR-30a-5p could be a potential therapeutic strategy in breast cancer. Highlights: LDHA is a novel direct target of miR-30a-5p. miR-30a-5p dampens glycolysis via inhibition of LDHA in vitro and in vivo. Glycolysis via miR-30a-5p is critical for breast tumor growth and metastasis. miR-30a-5p is negatively correlated with glycolysis in breast cancer patients.